An integrated multi-omics approach identifies the landscape of interferon-α-mediated responses of human pancreatic beta cells - Maikel L. Colli (Nature Portfolio, 2020)
The cytokine IFNα is expressed in the islets of individuals with type 1 diabetes and contributes to local inflammation and destruction of beta cells. Here, the authors provide a global multiomics view of IFNα-induced changes in human beta cells at the level of chromatin, mRNA and protein expression.